A Qualitative Review Of Game Theory Models In Market Transactions - Benardi Benardi; Tanti Sugiharti; A. Sigit Pramono Hadi (International Journal of Business Law, Business Ethic, Business Comunication & Green Economics, 2024)
This study is a qualitative review of game theory models in market transactions, focusing on the dynamics of matching between agents with diverse preferences. By examining various recent literatures, this research identifies two competition regimes in the market related to connectivity levels, namely "weak competition" and "strong competition." In weak competition, the outcomes tend to be more evenly distributed among agents, whereas in strong competition, there is significant unfairness between sides of the market. This study emphasizes the importance of effective matching system design to enhance agent welfare. The findings also indicate that understanding agent preferences and stakeholder participation in system design are crucial for creating fair and efficient markets. Although this research provides important insights into market interactions, several limitations should be noted, including the lack of representation of external factors and specific market contexts. Therefore, further research that combines quantitative and qualitative approaches is needed to gain a deeper understanding of market dynamics.